Dengue Fever: A Comprehensive Review of Diagnosis and Management - Shete, Meghanath B.; Saraogi, Gaurav Kant; Parashar, Ashish Kumar (Anti-Infective Agents, 2026)
The 21st century has witnessed a dramatic surge in dengue pandemics, establishing it as a major global health concern. Dengue is a debilitating viral disease caused by the dengue virus, a member of the Flaviviridae family. Transmission primarily occurs through the bite of infected female Aedes mosquitoes, particularly Aedes aegypti. The global incidence of dengue has increased dramatically in recent decades, with an estimated 390 million infections occurring annually. Clinical manifestations of dengue vary widely, ranging from mild febrile illness to severe dengue, which can be life-threatening. Despite extensive research efforts, no specific antiviral therapy for dengue exists, underscoring the critical importance of early and accurate diagnosis for effective management and mortality reduction. However, the lack of widely available and reliable diagnostic tools, particularly in resource-limited settings, poses a significant challenge. This comprehensive review provides an in-depth overview of dengue, encompassing its virology, pathogenesis, clinical presentation, and the latest advancements in diagnostic techniques. We delve into both conventional methods, such as serological and molecular tests, and emerging diagnostic approaches. Furthermore, we discuss current management strategies for dengue, including supportive care, vector control measures, and ongoing efforts in vaccine development. In conclusion, effectively combating dengue necessitates a multifaceted approach involving continuous research and development of innovative diagnostic tools, effective antiviral therapies, and the realization of a safe and effective vaccine.
Keywords: vaccine development